Detection of Polymorphism on Voltage-gated Sodium Channel Gene of Indonesian Aedes aegypti Associated with Resistance to Pyrethroids - Budi Mulyaningsih; Sitti Rahmah Umniyati; Tri Baskoro Tunggul Satoto; Ernaningsih Ernaningsih; Dwi Aris Agung Nugrahaningsih (The Prodia Education and Research Institute (PERI), 2018)
BACKGROUND: Aedes aegypti is a vector of several pathogens including dengue virus. Vector control is an effective way to break the transmission but unfortunately constant use of insecticides ultimately causes vector resistance. Pyrethroids have been used for about 15 years to combat Ae. aegypti in Yogyakarta Province, Indonesia. Single amino acid substitutions in the voltagegated sodium channel associated with pyrethroid resistance constitute one of the main causative factors of knockdown resistance (kdr). The aim of this study is to detect resistant status to cypermetrine and polymorphism on the voltagegated sodium channel gene of Ae. aegypti from 2 dengue endemic areas in Yogyakarta Province (Yogyakarta city and Sleman district).METHODS: Pyrethroid resistance in Ae. aegypti mosquitoes was detected by using CDC Bottle Bioassay. To detect the polymorphism on the voltage-gated sodium channel gene of Ae. aegypti analyses were conducted by using PCR and direct DNA squencing with primers AaSCF1 and AaSCR4 for S989P, I1011M (or V), L1014F sites, and AaSCF7 and AaSCR7 for the F1534C site.RESULTS: According to bioassay, the results for Ae. aegypti from Yogyakarta city (93% mortality) and Sleman district (88% mortality) suggest the possibility of resistance to cypermethrin. We observed polymorphism on voltagegated sodium channel gene on site F1534C (heterozygous).CONCLUSION: The findings provide early evidence that the use of cypermethrin (pyrethroids) in Yogyakarta city and Sleman district, Yogyakarta Province, Indonesia is reducing its effectiveness to control Ae. aegypti. Recommendations include additional tests for confirmation.KEYWORDS: Aedes aegypti, dengue virus, cypermethrin, Bioassay, Yogyakarta